Juventude e identidade: um olhar do jovem sobre si mesmo - Chinkevicz, Josane Fernanda Lisboa (2014)
The theme of "identity" in line with Cultural Studies, leverages a look at the current generation of young people: their habits, cultural practices, social movement, which, composing a complex network of meanings. his reflection suggests a focus on the audience that attends ProJovem Urban Program in Santa Catarina, trying to analyze the perception of these young people (documentary production) about their own identities. The youth served by the program are " excluded communities " in urban areas . Are workers, parents and homemakers . Many have already left school a long time and try to go back to school again and regain lost seats and / or seeking a better professional qualification time. Analyzing traces of life of these subjects studied , one realizes that they bring diverse social and cultural experiences , come from different localities / municipalities of Santa Catarina . They come from a complex universe where references to withdraw their identities , this reality that social projects , in general , should be prepared to know and recognize . Projovem Urban Programme aims to bring school education vocational qualification , a vision of citizenship training . Projects and programs that youths hear and create spaces for dialogue between them and their teachers are the ones who best qualify for learning more broadly